ANALISIS STRATEGI PENGEMBANGAN BISNIS CIRCLE A COFFEE COMPANY: - Mustopa, Jaka; Sudono, Agus; Khosihan, Aan (JURNAL PARIWISATA VOKASI, 2023)
Circle A Coffee Company is a business that processes coffee beans, but at this time there has been no business development from year to year. The purpose of this research is to help the company to develop its business for the long term and be able to face all the obstacles that will arise both from internal and external factors later. Based on the existing problems, the researchers conducted research on the company using descriptive qualitative methods. Data collection was carried out by means of observation, interviews and documentation to be processed as a result of the research. In this study, the analysis is divided into two parts, namely internal factor analysis and external factor analysis using SWOT matrix analysis. Based on the analysis of descriptive qualitative methods that have been carried out, one of the strategic recommendations that Circle A Coffee Company needs to do is to improve the quality of Human Resources, take advantage of technological advances in the modern era and maximize promotional programs or discounts to increase sales figures at the company.